A Two‐Martian Years Survey of the Water Vapor Saturation State on Mars Based on ACS NIR/TGO Occultations. Issue 1 (30th December 2022) - Fedorova, Anna; Montmessin, Franck; Trokhimovskiy, Alexander; Luginin, Mikhail; Korablev, Oleg; Alday, Juan; Belyaev, Denis; Holmes, James; Lefevre, Franck; Olsen, Kevin; Patrakeev, Andrey; Shakun, Alexey
Abstract: On Mars, condensation is the major factor constraining the vertical distribution of water vapor. Recent measurements of water and temperature profiles showed that water can be strongly supersaturated at and above the level where clouds form during the aphelion and perihelion seasons. Since 2018, the near‐infrared spectrometer (NIR) of the Atmospheric Chemistry Suite onboard the Trace Gas Orbiter has measured H2 O and temperature profiles using solar occultation in the infrared from below 10 to 100 km of altitude. Here, we provide the first long‐term monitoring of the water saturation state. The survey spans 2 Martian years from Ls  = 163° of MY34 to Ls  = 170° of MY36. We found that water is often supersaturated above aerosol layers. In the aphelion season, the water mixing ratio above 40 km in the mid‐to‐high latitudes was below 3 ppmv and yet is found to be supersaturated. Around the perihelion, water is also supersaturated above 60 km with a mixing ratio of 30–50 ppmv. Stronger saturation is observed during the dusty season in MY35 compared to what was observed in MY34 during the Global Dust Storm and around the perihelion. Saturation varied between the evening and morning terminators in response to temperature modulation imparted by thermal tides. Although water vapor is more abundant in the evening, colder morning temperatures induce a daily peak of saturation. This data set establishes a new paradigm for water vapor on Mars, revealing that supersaturation is nearly ubiquitous, particularly during the dust season, thereby promoting water escape on an annual average. Plain Language Summary: The rate of water loss from Mars depends on hydrogen, the main product of the H2 O photodissociation escaping from the upper atmosphere. The ability of water to reach high altitudes and to be a direct source of atomic hydrogen is limited by cloud formation, which holds water vapor in the lower atmosphere. This process is regulated by temperature and pressure. Condensation starts when the temperature is cold enough and condensation nuclei (CN) (e.g., small dust particles) are available. If CN are lacking, or their sizes are too small, or the temperature drops too fast, then water vapor becomes supersaturated. Recent studies have shown that Martian water vapor is often supersaturated. Here, we present the first seasonal cycle of the saturation state from simultaneous measurements of water and temperature during two Martian years by Atmospheric Chemistry Suite on the Trace Gas Orbiter. Our results show that supersaturation is typical on Mars. It occurs above clouds both in the aphelion and perihelion seasons as well as in the lower polar atmosphere. We demonstrate supersaturation to be an important factor facilitating the escape of water. Unlike the Earth, water easily penetrates the upper atmosphere and reaches photodissociation altitudes. Key Points: Long‐term observations of H2 O saturation state in the atmosphere of Mars show that supersaturation is nearly ubiquitous above aerosol layers During the dusty season, the supersaturation is stronger in MY35 compared to MY34 More water was found in the evening terminator and stronger supersaturation in the morning terminator